Posted by **Evelina** on Saturday, November 12, 2011 at 9:06am.

Please help me how to do this:

1) 1 + sina*cosa / (cosa + sina)^2 =

2) sina + cosa / 1- 2sin^2a =

- trig -
**Reiny**, Saturday, November 12, 2011 at 9:27am
Are you sure the first one isn't

( 1 + 2sina cosa)/(cosa + sina)^2 ?

because then it would be

= (sin^2a + cos^2a + 2sina cosa)/(cosa + sina)^2

= (sina + cosa)^2/(cosa + sina)^2

= 1

2nd:

(sina + cosa)/(1 - 2sin^2a)= (sina + cosa)/(sin^2a + cos^2a - 2sin^2a)

= sina+cosa)/( cos^2a - sin^2a)

= (sina + cosa)/( cosa - sina)(cosa+sina) )

= 1/(cosa - sina)

- trig -
**Evelina**, Saturday, November 12, 2011 at 9:37am
oh yes, I wrote the first one wrong.

THANK YOU

## Answer This Question

## Related Questions

- Maths - Hi, can someone give me the answer to this question: secA-tanA=1/4. Find...
- further mathematics - Let P=(cosA sinA) (sinA cosA) Q=(cosB sinA) (sinB cosA) ...
- Maths - Prove that [sinA/(1-cosA)-(1-cosA)/sinA]*[cosA/(1+sinA)+(1+sinA)/cosA]=...
- trig - Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA
- trig - I need to count this: a) 1-tg^2a/1+ctg^2a, when sina =2/3 b) 1-tg^2a/1-...
- trig - prove that :cosA-sinA+1/cosA+sinA-1=cosecA+cotA
- trig - Prove : (sinA-cosA+1)/(sinA+cosA-1) = (1+sinA)/cosA
- Maths, Divine International Public School - If 15Cot=8, find (1+SinA)(1-SinA)/(1...
- trigonometry - x×sin^3A=y , cos^3A = sinA × cosA , x×sinA= y×cosA , then prove ...
- maths(trigonometry) - prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA

More Related Questions